INNOVATION STRUCTURE FOR RESEARCH ACTIVITIES AT THE UNIVERSITY - Anna Y. Yakovleva-Chernysheva; Ekaterina V. Belyaeva; Inna Yu. Yakunina (Высшее образование в России, 2016)
The article deals with the role of the International Innovative University in the national science development. The innovative structure for the of the organization research activities attheUniversity including research institutes, sceintific laboratories, and innovation, technology and consulting centres is considered. The university accomplishes fundamental research, applied research and development, implementation of study results into educational process and into practice. The university possesses its own business incubator for commercialization of study research and for aquiring professional skills by students.